Gametogonic and sporogonic development of Sarcocystis cruzi of cattle in experimental pups - PANDIT, B A; BHATIA, B B (The Indian Journal of Animal Sciences, 2013)
The experimental gametogonic and sporogonic development as well as pathogenicity in definitive host of Sarcocystis cruzi was studied. Microsarcocysts of S. cruzi from muscles of different organs and tissues of cattle were fed to 6 healthy pups. Two of these infected pups were sacrificed on day 8 and 10 post-infection (DPI) for histological study. Four more pups, fed uninfected tissue from the same organs, served as control. The infected pups were found to be shedding sporocysts in their faeces from 9 to 10 (average 9.4) DPI. The peak shedding of sporocysts/oocysts ranged from 23 to 27 days. The patent period ranged from 39 to 76 (average 55.25) days. Sporulated oocysts and sporocysts measured 20-23 x 15-18.75 (average 19.77 x 16.81 um) and 2.25-17.50 x 8.75-10 .um (average 14.18 x 9.85 um), respectively. The intestinal scrapings of pups, revealed different gametogonic stages of the parasite in the parasitophorous vacuoles in the lamina propria, beneath the epithelial lining of crypts or within the villi. The gametogonic and sporogonic developmental stages studied in the present investigation were almost identical to the description given by earlier workers. Clinically all the pups showed inappetence, diarrhoeic faeces with shreds of mucus between 4 and 6 DPI. Otherwise, no significant clinical sign was observed in the experimental pups fed heavily infected cattle tissue with S. cruzi.